Carbon flux estimation for Siberia by inverse modeling constrained by aircraft and tower CO2 measurements. Issue 2 (31st January 2013) - Saeki, T.; Maksyutov, S.; Sasakawa, M.; Machida, T.; Arshinov, M.; Tans, P.; Conway, T. J.; Saito, M.; Valsala, V.; Oda, T.; Andres, R. J.; Belikov, D.
Abstract : [1] Being one of the largest carbon reservoirs in the world, the Siberian carbon sink however remains poorly understood due to the limited numbers of observation. We present the first results of atmospheric CO2 inversions utilizing measurements from a Siberian tower network (Japan‐Russia Siberian Tall Tower Inland Observation Network; JR‐STATION) and four aircraft sites, in addition to surface background flask measurements by the National Oceanic and Atmospheric Administration (NOAA). Our inversion with only the NOAA data yielded a boreal Eurasian CO2 flux of −0.56 ± 0.79 GtC yr −1, whereas we obtained a weaker uptake of −0.35 ± 0.61 GtC yr −1 when the Siberian data were also included. This difference is mainly explained by a weakened summer uptake, especially in East Siberia. We also found the inclusion of the Siberian data had significant impacts on inversion results over northeastern Europe as well as boreal Eurasia. The inversion with the Siberian data reduced the regional uncertainty by 22% on average in boreal Eurasia, and further uncertainty reductions up to 80% were found in eastern and western Siberia. Larger interannual variability was clearly seen in the inversion which includes the Siberia data than the inversion without the Siberia data. In the inversion with NOAA plus Siberia data, east Siberia showed a larger interannual variability than that in west and central Siberia. Finally, we conducted forward simulations using estimated fluxes and confirmed that the fit to independent measurements over central Siberia, which were not included in inversions, was greatly improved. Key points: CO2 inversion is performed using Siberian data and background data The inclusion of Siberian data in the inversion weakens a boreal Eurasian sink Siberian data reduce flux uncertainties over Siberia and northeastern Europe